Analysis of the Level of Self-Confidence, Sense of Responsibility, Future-Oriented Attitude Affects Business Success Through Managerial Ability as a Mediating Variable - Adiyani, Rini; Darsono, Darsono; Sumarto, Laksono; Ripta, Dwinanda; Febrianto, Alvano (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the effect of self-confidence, sense of responsibility, and orientation on business success through managerial ability as a mediating variable. The research method used is quantitative. The population in this study were sheep farmers in Lembang Bandung, namely 80 farmers. The sampling technique of this research is probability sampling with a purposive sampling technique. The minimum sample size required is 68 respondents. Research data is obtained from primary data and secondary data. Data were obtained through respondents' answers using questionnaires. The data source refers to information obtained directly from consumers who are sampled respondents. The data analysis technique in this study uses Partial Least Square (PLS) with SMARTPLS Software's help. The results of this study show that a level of self-confidence, a sense of responsibility, and a future-oriented attitude have a significant effect on the success of the sheep breeder business and managerial ability can mediate the relationship between the level of self-confidence, a sense of responsibility, and a future-oriented attitude towards business success.